Institucionalizacija in komercializacija subkulturnih grafitov - Zidarič, Tjaša (Etnolog. Nova vrsta (Ljubljana), 2011)
The article addresses the phenomenon of subculture graffiti being institutionalised and commercialised when they are moved from their authentic street context to the sphere of official art or various branches of commercial culture. It mainly focuses on the question whether graffiti can be considered a form of art. The theme is connected with the issues of how art is conceived in the present and reveals that what we consider art is primarily a construct of society and culture. In this sense, the phenomenon of the institutionalisation of graffiti in art institutions is an example of a specific social context, in which graffiti are produced, presented and accepted as art, because it is essentially the art institution that constructs new meanings for their evaluation. The author complements the theoretical premises with material gathered as part of a field research in the form of statements of graffiti creators and photographs of graffiti in Ljubljana.
Keywords: ethnology; etnologija; grafiti; subculture; subkultura; street art; ulična umetnost; anthropology of art; likovna umetnost; visual arts; urbana kultura; sociologija kulture; sociologija umetnosti; antropologija umetnosti; gaffiti; urban culture